2021
DOI: 10.3389/fnins.2021.734001
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic and Neuronal Apolipoprotein E Isoforms Differentially Affect Neuronal Excitability

Abstract: Synaptic changes and neuronal network dysfunction are among the earliest changes in Alzheimer’s disease (AD). Apolipoprotein E4 (ApoE4), the major genetic risk factor in AD, has been shown to be present at synapses and to induce hyperexcitability in mouse knock-in brain regions vulnerable to AD. ApoE in the brain is mainly generated by astrocytes, however, neurons can also produce ApoE under stress conditions such as aging. The potential synaptic function(s) of ApoE and whether the cellular source of ApoE migh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 56 publications
2
24
0
Order By: Relevance
“…ApoE is present in a subset of synapses, co-localizing to 18–36% of synapses [ 459 ]. A recent study observed a synapse-associated localization of apoE in primary neuron cultures, in which both apoE3 and apoE4 co-localize with vGlut1-positive pre-synaptic terminals [ 460 ]. ApoE co-localizes with synaptic markers in both healthy controls and AD subjects, pointing towards a not purely pathological role of apoE at synaptic terminals.…”
Section: Apoe In Alzheimer’s Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…ApoE is present in a subset of synapses, co-localizing to 18–36% of synapses [ 459 ]. A recent study observed a synapse-associated localization of apoE in primary neuron cultures, in which both apoE3 and apoE4 co-localize with vGlut1-positive pre-synaptic terminals [ 460 ]. ApoE co-localizes with synaptic markers in both healthy controls and AD subjects, pointing towards a not purely pathological role of apoE at synaptic terminals.…”
Section: Apoe In Alzheimer’s Diseasementioning
confidence: 99%
“…Further on, regarding astrocytic implications in neuroinflammation, sex-mediated differences in the astrocytic response towards an inflammatory stimulus have been described in primary astrocytic cell lines [ 554 , 555 ]. ApoE can target synapses and impact neuronal activity differently if released by neurons or astrocytes [ 460 ]. Live-calcium imaging techniques in vitro cultured neuron models have evidenced that neuron-released apoE induces the highest neuronal firing in the presence of apoE3 and not apoE4, whereas astrocytic-derived apoE induces the strongest neuronal firing with apoE4 [ 460 ].…”
Section: Apoe In Alzheimer’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The ApoE expressed in microglia is involved in switching between homeostatic and disease-associated phenotypes [ 57 ]. ApoE3 KI neurons show increased neuronal activity compared to ApoE4 KI neurons [ 58 ]. The overexpression of human ApoE4 in neurons results in the hyperphosphorylation of the microtubule-associated protein tau [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, as with overall morphology, APOE4 ‐related synaptic protein loss is exacerbated by stressors, injury, and neuronal ApoE4 expression (Buttini et al, 1999, 2000, 2010; Lin et al, 2016; Zhang et al, 2021). Similarly, in vitro studies suggest a possible loss of excitatory and inhibitory synapses and impaired maturational rate via glial‐derived ApoE4 (Konings et al, 2021; Nwabuisi‐Heath et al, 2013), supporting the importance of both glial and neuronal ApoE in synapse formation and maintenance.…”
Section: Hit 1: Neurodegeneration and Neurodevelopmentmentioning
confidence: 91%